Methodology of Teaching Economics and Accounting in a Market Economy - Kazakova Zulayxo Salaxiddinovna (Periodica Journal, 2023)
Conducting classes in economics at university will allow students to master economic theory and the economic concepts corresponding to it, instill in them the skills of competent economic behavior, master the system of norms characteristic of various economic systems. The purpose of the article is to study the organizational and methodological process of teaching economics in universities
Keywords: knowledge; skills; abilities